Методические особенности оценки процессов заиления искусственных водохранилищ на основе метода аналогии - Дубовик, Денис Дмитриевич (НТУ "ХПИ", 2018)
Методика оценки процесса заиления искусственных водохранилищ (аналогов) на основе известных характеристик заиления специально выбранного водоема-прототипа. Критериями выбора водоема-прототипа служит мера аналогии, рассчитанная на основе основных характеристик – морфологических, гидрологических, физико-химических и биологических сравниваемых водохранилищ. В основу методики в работе предлагается использовать наборы комплексных критериев различного уровня полноты, определяемых количеством частных критериев, входящих в комплексный критерий с соответствующими весовыми коэффициентами на основе максимального уровня аналогии, который определяется специальной мерой – коэффициентом несоответствия или обратным ему коэффициентом аналогии. Последний определяется как модуль отношения разности критериев аналогии сравниваемых водохранилищ к их среднему значению. Выполнен сравнительный анализ значений критериев подобия водохранилищ – аналогов (водохранилищ каскада) и водохранилища – прототипа и сравнительный анализ значений критерия подобия всех сочетаний пар водохранилищ Днепровского каскада. На этой основе построена матрица отличий водохранилищ аналогов, которая позволяет оценить возможность применения метода подобия, используя в качестве аналога одно из водохранилищ каскада, если оно удовлетворяет требованиям аналогии.

The similarity of artificial reservoirs (AR) is determined by the proximity of their parameters and characteristics. In this regard, the selection of the criteria for analogy is, in fact, the task of multicriteria comparative analysis, which dictates the need, on the one hand, to select the parameters of artificial reservoirs to a decisive degree, determining those characteristics of the reservoirs that reflect their studied properties and, accordingly, the synthesis of the criteria for analogy, providing a solution to the problem of choosing a reservoir-prototype for the analyzed reservoir-analogue. A methodology for estimating the process of siltation of artificial reservoirs (analogues) based on known silt characteristics of a specially selected prototype reservoir is developed. The criterion for choosing a reservoir prototype is a measure of analogy, calculated on the basis of the main characteristics-morphological, hydrological, physico-chemical and biological compared reservoirs. The method is based on the use of sets of complex criteria of various levels of completeness determined by the number of particular criteria included in the complex criterion with the corresponding weight coefficients on the basis of the maximum level of analogy, which is determined by a special measure the coefficient of nonconformity or the inverse coefficient of analogy. The latter is defined as the ratio of the differen ce between the criteria for the analogy of the reservoirs being compared to their mean value. A comparative analysis of the values of similarity criteria for reservoirs - analogues (cascade reservoirs) and a reservoir - a prototype and a comparative analysis of the values of the similarity criterion for all combinations of pairs of reservoirs of the Dnieper cascade. On this basis, a matrix of differences in the reservoirs of analogues is constructed, which makes it possible to estimate the possibility of using the similarity method, using as an analogue one of the reservoirs of the cascade, if it satisfies the requirements of analogy.
Methodical peculiarities of estimation of processes of seization of artificial water reservoirs based on the analogy method
Keywords: критерий подобия; инфомационная модель; весовой коэффициент; матрица отличий; коэффициент аналогий; модель-прототип; similarity criterion; information model; weight coefficient